2017
DOI: 10.1016/j.idm.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling for Zoonotic Visceral Leishmaniasis dynamics: A new analysis considering updated parameters and notified human Brazilian data

Abstract: Brazil is one of the highest endemic countries for Zoonotic Visceral Leishmaniasis: according to the Brazilian Ministry of Health, the annual number of new human cases and deaths due to this disease has been increasing for the last 20 years. In addition, regarding the Americas, the specific relationship between canine and human for Visceral Leishmaniasis dynamics is still not well understood. In this work we propose a new model for Zoonotic Visceral Leishmaniasis, based on the models previously published by Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…In addition to the technical issues, the most controversial aspect of canine reservoir elimination has been the ethical question considering the emotional involvement of both the owners and the subjects involved in the culling procedure [33][34][35][36][37][38][39][40][41][42][43][44][45][46]. However, it is noteworthy that HVL is a disease with high lethality if untreated, and it is in the process of geographical expansion [3,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the technical issues, the most controversial aspect of canine reservoir elimination has been the ethical question considering the emotional involvement of both the owners and the subjects involved in the culling procedure [33][34][35][36][37][38][39][40][41][42][43][44][45][46]. However, it is noteworthy that HVL is a disease with high lethality if untreated, and it is in the process of geographical expansion [3,47].…”
Section: Discussionmentioning
confidence: 99%
“…The use of insecticide-impregnated collars has been recommended as the most effective measure among those cited above [43,[53][54][55]. Silva et al [56] demonstrated a reduction of 15% (p = 0.004) in Montes Claros, MG, Brazil, and 60% (p <0.001) in Fortaleza, CE, Brazil, in the vector population of captured.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when comparing the respective sensitivity test values in three other sand fly-associated 230 parameter sets, sand fly bite rate (parameter ID 11), probability of a susceptible dog becoming 231 infected when bitten by an infected sand fly (parameter ID 13) and proportion of female sand flies 232 unobserved (parameter ID 15), in each case we found the median average infection prevalence 233 to differ by over 10% across the range of values tested ( Figure 6, panels (11,13,15)).…”
mentioning
confidence: 95%
“…Da mesma forma, a modelagem matemática tem sido aplicada aos estudos das leishmanioses visando representar a forma como a infecção se espalha numa população, permitindo a avaliação e/ou criação, ainda que de forma teórica, de instrumentos que possam, essencialmente, auxiliar nas ações de prevenção e/ou controle da dispersão da doença em foco (COSTA et al 2012;SEVÁ et al, 2016;SHIMOZAKO et al, 2017a;SHIMOZAKO et al, 2017b;HUSSAINI et al, 2017). Nesse sentido, este projeto pretende ampliar a compreensão da dinâmica de transmissão da infecção e contribuir assim para uma melhor elaboração e/ou direcionamento de medidas de prevenção e controle em nível de saúde Pública, por meio da identificação de áreas prioritárias, da avaliação das coberturas das estratégias de controle químico e do reservatório canino, da observação de fatores associados à infecção canina e da verificação da efetividade da eutanásia como medidas de controle.…”
Section: Fatores Associados Ao Risco De Infecção Em Cãesunclassified